Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan di Novotel Bali Nusa Dua - Pramesti, Ni Kadek Ratih; Suarmana , I Wayan Restu (Penerbit Goodwood, 2024)
Purpose: The purpose of this study is to describe and explain the performance of employees who are influenced by the work environment. This research was conducted at Novotel Bali Nusa Dua Hotel & Residencies. Research methodology: This type of research uses quantitative methods with a population of 62 employees.Results: The data analysis technique used in this study is Simple Linear Regression Analysis, t-test, and Coefficient of Determination (R2). The data analysis technique used in the study was to process data through the SPSS version 25 statistics program for Windows. The results of the hypothesis in a partial t-test obtained that the t count of the Work Environment variable is 8.199 where the probability is greater than t table 1.669 with a significant level of 0.000 less than 0.05 which means that there is a significant influence between the work environment and employee performance at Novotel Bali Nusa Dua Hotel & Residences.Conclusions: This study concluded that there is a significant influence between the work environment on employee performance at Novotel. The positive relationship indicates that the better the work environment provided, the higher the employee performance. The results of the t test and the coefficient of determination reinforce that the work environment is an important factor that is able to explain 52.8% of the variation in employee performance.Limitations: The work environment has a strong enough influence on employee performance, this is seen from the results of the coefficient of determination, the work environment variable has a contribution of 52.8% to employee performance, and the remaining 47.2% is influenced by other variables not examined in this study.Contribution: This research provides a practical contribution for company management in understanding the importance of creating a conducive work environment to improve employee performance. In addition, academically, this research adds empirical references regarding the relationship between work environment and employee performance, especially in the context of the hospitality industry.Keywords: Keywords: Employee Performance, Leadership Style, Work Motivation How to Cite: Pramesti, N, K, R. Suarmana, I, W, R. (2024). Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan di Novotel Bali Nusa Dua. Jurnal studi perhotelan dan pariwisata, 3(1), 21-29.